Episotological characteristics of dog dirofilariasis in the city of Kharkiv - Yevstafievа V.; Kryvoruchenko, D. (Scientific Progress & Innovations, 2022)
Dirofilariasis is a disease caused by nematodes of the genus Dirofilaria, among which the most common species are D. immitis and D. repens. All over the world, these pathogens are registered among dogs, cats and humans. Despite significant advances in the field of dirofilariasis, the incidence of canine and severe infestations due to D. immitis parasitism continues to increase. The purpose of the research was to conduct monitoring studies of epizootological features of dirofilariasis in dogs in the city of Kharkiv. It was found that the spread of this infestation among the population of domestic dogs depends on many factors, such as the season, the way the animals are kept, age and breed characteristics. It was established that the average infestation of dogs with the causative agent of dirofilariasis in the city of Kharkiv according to the results of hemolarvoscopic and immunological studies is 28.30 %. Indicators of the intensity of invasion by microfilaries ranged from 8 to 218 larvae per cm3 of blood. The age dynamics of dirofilariasis is characterized by maximum damage in dogs aged 5–8 years, where the extent of infestation reaches 41.26 %. The least infested were young dogs under the age of two (13.95 %). It was found that the most susceptible to dirofilaries are Rottweiler dogs (51.52 % infestation extent), Caucasian Shepherd Dog (47.83 %), German Shepherd Dog (41.51 %), Labrador Retriever (40.54 %), Alaskan Malamute (30 %); half-breeds (37.74 %) and purebred dogs (32.56 %). Seasonal fluctuations are characterized by the peak of invasion in the springsummer period of the year, where the extent of invasion varied from 28.65 to 39.27 %. Dirofilariasis occurs in 74.18 % of infected dogs in the form of associations of dirofilaries and nematodes – trichurises, toxocares, dipylidies, uncinaries, as well as the simplest organisms – cystoisospores. A total of 14 types of mixinvasions have been established. Selected associations for dirofilariasis consist of two (40.11 %), three (24.73 %), four (7.69 %) and five (1.65 %) causative agents of invasions. The obtained results of monitoring studies on the epizootological features of dirofilariasis in dogs make it possible to facilitate the diagnosis of this infestation, and also, taking into account the established mixinvasions, to effectively carry out treatment and preventive measures.